Paromomycin is a more effective selection agent than kanamycin in Arabidopsis harboring the neomycin phosphotransferase II transgene - Colton P. Goodman; Victoria N. Padgett; Elijah R. Evans; Albrecht G. von Arnim (PLoS ONE, 2025)
Neomycin phosphotransferase II (nptII) is a selectable marker gene that is commonly used in plant molecular genetics and crop improvement, helping researchers to identify and select transgenically modified plants. The NPTII enzyme binds to and phosphorylates the aminoglycoside family of antibiotics, which are known translation inhibitors. Once the aminoglycoside is phosphorylated it is unable to bind to the ribosome and can no longer disrupt translation. Currently, the most widely used selection agent for screening NPTII expressing seedlings is kanamycin. Because the nptII transgene is frequently silenced epigenetically, kanamycin can be too toxic to seedlings that weakly express NPTII, leading to false negatives and making it harder to accurately identify transgenic plants. In this study we investigate the related aminoglycoside, paromomycin, as an alternative, non-lethal, selection agent to kanamycin across a series of transgenic Arabidopsis lines with varying NPTII expression. We investigated phenotypes of transgenic seedlings during and after antibiotic exposure. Seedling pigmentation and size are useful phenotypes for selecting seedlings with low nptII expression. Additionally, monitoring the photosynthetic efficiency and flowering time can help reduce the risk of false-positive results when treating seedlings with paromomycin.